PELAKSANAAN PENDIDIKAN KARAKTER PADA SEKOLAH JENJANG SD SE-KECAMATAN BATUKLIANG UTARA - LALU MUHAMAD NASIR; ERLAN HARTAWAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to describe the teacher's steps in implementing social care character education at the elementary school level in Batukliang Utara District. This research is a qualitative descriptive study. Researchers conducted observations, interviews, and documentation with the research subjects, namely principals, teachers, and students. Data analysis uses data reduction, data display, and drawing conclusions. The data validity technique uses technical triangulation and source triangulation. The results of the study show that the implementation of social care character education is carried out through; (1) self-development in the form of routine activities with infaq, the teacher provides an example in the form of direct examples, the teacher also carries out spontaneous activities by reprimanding students who are indifferent to friends, and through conditioning by installing rules, student codes of ethics and posters related to social care, teachers also condition the class with group work; (2) school culture development is carried out with school activities in accordance with social care character indicators; (3) the integration of social care characters in the subject matter; and (4) familiarize students to empathize with the bereaved family or school neighbors by bringing Pelangar (sasak culture). ABSTRAKPelaksanaan pendidikan karakter peduli sosial di jenjang SD Se-Kecamatan Batukliang Utara. Penelitian ini merupakan penelitian deskriptif kualitatif. Peneliti melakukan observasi, wawancara, dan dokumentasi dengan subjek penelitian yaitu kepala sekolah, guru, dan siswa. Analisis data menggunakan reduksi data, display data, dan penarikan kesimpulan. Teknik keabsahan data menggunakan triangulasi teknik dan triangulasi sumber. Hasil penelitian menunjukkan pelaksanaan pendidikan karakter peduli sosial dilakukan melalui; (1) pengembangan diri berupa kegiatan rutin dengan infaq, guru memberikan keteladanan berupa contoh langsung, guru juga melaksanakan kegitan spontan dengan menegur siswa yang acuh dengan teman, serta melalui pengkondisian dengan memasang tata tertib, kode etik siswa dan poster berkatian dengan peduli sosial, guru juga mengkondisikan kelas dengan kerja kelompok; (2) pengembangan budaya sekolah dilaksanakan dengan kegiatan sekolah sesuai dengan indikator karakter peduli sosial; (3) pengintegrasian karakter peduli sosial dalam materi pelajaran; dan (4) membiasakan siswa untuk turut berempati kepada keluarga siswa atau tetangga sekolah yang berduka dengan membawa pelangar (budaya sasak).